Reliability analysis of the anti-sliding of a retaining wall subjected to seismic loads. (October 2021) - Huang, Xiao-Cheng; Xu, Xiao-Di; Chen, Qiu-Nan; Liu, Yun-Fu
Geotechnical engineering involves various types of uncertainties, as it always deals with highly variable natural materials. Reliability-based design/analysis can play at least a complementary role in the design approach. In this paper, reliability analysis of anti-sliding of retaining wall with the parameters treated as random variables is performed based on the concept of random fields. Both friction angle and cohesion of soils near the interface along the base of retaining wall are treated as Gaussian fields. The spatial correlation and cross correlation of the variables are calculated by a specific covariance function and the seismic loads act on retaining walls are also taken into account. Examples are illustrated to verify the accuracy of the proposed approach. It is found from the numerical results that the spatial correlation of shear strength has an important influence on the probability of the anti-sliding failure of retaining wall. Moreover, the numerical results obtained from the proposed method are in full agreement with those obtained from Monte Carlo simulations. Therefore, the proposed method provides a new view to study the stability of a retaining wall subjected to seismic loads.